Maternal body mass index and post‐term birth: a systematic review and meta‐analysis. (13th January 2017) - Heslehurst, N.; Vieira, R.; Hayes, L.; Crowe, L.; Jones, D.; Robalino, S.; Slack, E.; Rankin, J.
Summary: Post‐term birth is a preventable cause of perinatal mortality and severe morbidity. This review examined the association between maternal body mass index (BMI) and post‐term birth at ≥42 and ≥41 weeks' gestation. Five databases, reference lists and citations were searched from May to November 2015. Observational studies published in English since 1990 were included. Linear and nonlinear dose–response meta‐analyses were conducted by using random effects models. Sensitivity analyses assessed robustness of the results. Meta‐regression and sub‐group meta‐analyses explored heterogeneity. Obesity classes were defined as I (30.0–34.9 kg m −2 ), II (35.0–39.9 kg m −2 ) and III (≥40 kg m −2 ; IIIa 40.0–44.9 kg m −2, IIIb ≥ 45.0 kg m −2 ). Searches identified 16, 375 results, and 39 studies met the inclusion criteria ( n  = 4, 143, 700 births). A nonlinear association between maternal BMI and births ≥42 weeks was identified; odds ratios and 95% confidence intervals for obesity classes I–IIIb were 1.42 (1.27–1.58), 1.55 (1.37–1.75), 1.65 (1.44–1.87) and 1.75 (1.50–2.04) respectively. BMI was linearly associated with births ≥41 weeks: odds ratio is 1.13 (95% confidence interval 1.05–1.21) for each 5‐unit increase in BMI. The strength of the association between BMI and post‐term birth increases with increasing BMI. Odds are greatest for births ≥42 weeks among class III obesity. Targeted interventions to prevent the adverse outcomes associated with post‐term birth should consider the difference in risk between obesity classes.